Adaptive leadership and open management practices - Cherry Vu; Rob England (Journal of State Management, 2024)
An increasingly volatile, uncertain, complex, and ambiguous (VUCA) world requires better working methods, which can only be unlocked by better work management methods. The authors summarize global trends in working as “open” and apply this to open management and work. They also recommend some implications for government entities to achieve effectiveness in their operations in a changing environment.